Training experience for future social workers in USА - Ганна Анатоліївна Рідкодубська (Ukrainian Journal of Educational Studies and Information Technology, 2018)
The article examines the training of future social workers in the United States and describes the ways of transforming positive experiences into the modern educational system of Ukraine. The author examines the main stages of the formation of American vocational training of social workers, which characterize the system of training, which was launched in 1898. The main differences in the training future social workers in the United States, the author notes the widespread use of practical forms of knowledge acquisition, a high percentage the tasks of the student's independent learning activities, the presence of slight specialization and a competent approach to the results of education.